Vitamin C in dermatology - Pumori Saokar Telang (Wolters Kluwer Medknow Publications, 2013)
Vitamin C is a potent antioxidant drug that can be used topically in dermatology to treat and prevent changes associated with photoageing. It can also be used for the treatment of hyperpigmentation. Because it is unstable and difficult to deliver into the dermis in the optimum dosage, research is being directed to find stable compounds of Vitamin C and newer methods of delivery of Vitamin C into the dermis.